Hubungan Indeks Massa Tubuh dan Lingkar Pinggang dengan Kualitas Tidur Mahasiswa Preklinik Program Studi Kedokteran, Fakultas Kedokteran Universitas Mulawarman: Relationship between Body Mass Index and Waist Circumference with Sleep Quality of Pre-clinical Students in Medical Study Program, Faculty of Medicine, Mulawarman University - Rohmi Pawitra Sari; Denny Jeffry Rotinsulu; Evi Fitriany (Jurnal Sains dan Kesehatan, 2021)
Sleep is defined as unconsciousness from which the person can be aroused by sensory or other stimuli. Long-term consequences of sleep deprivation increased the risk of hypertension, diabetes mellitus, obesity, heart failure, stroke, memory impairment as well as depression. Obesity is one of the factors that affect sleep quality. Obesity is associated with sleep quality through its effect of causing obstructive sleep apneu (OSA), increased proinflammatory cytokins and gastrointestinal disorders. This study aims to analyze the correlation between body mass index and waist circumference with the quality of sleep of the pre-clinical students of the Mulawarman University, Faculty of Medicine. This research is an observational analytic study with a cross-sectional approach. Sleep quality data were collected using the PSQI questionare while body mass index and waist circumference data were collected by measuring body height using microtoise, body weight using a weighing scale and waist circumference using an anthropometric band. The result showed that 81.2% of respondents had poor sleep quality, 28.2% of respondents with obesity category and 35.9% of respondents who had central obesity. The result of hypothesis testing using chi square showed that both body mass index and waist curcumference had a significant relationship with sleep quality (p=0.046 and p=0.027).